The Limiting Sequence and Proper Ratio of Lysine, Methionine and Threonine for Calves Fed Milk Replacers Containing Soy Protein - Wang, Jianhong (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
The limiting sequence and relative ratio of lysine (Lys), methionine (Met), and threonine (Thr) for calves about 2 mo of age fed milk replacers (MR) containing soy protein are not clearly defined. The objective of the study was to investigate the effect of supplementing MR containing 22% CP, half from soy protein concentrate (SPC, 40.56% CP, flour) and half from whey proteins, with Lys, Met, and Thr to estimate amino acid (AA) sequence and their relative ratio for calves about 2 mo of age. A method of partial deduction of AA was adopted. Twenty-four newborn calves (half males and half females, 40.7±0.9 kg of BW) were fed 1 of 4 MR diets for 56 d (n = 6/diet). The diets were supplemented with all (positive control) or with 2 of the 3 AAs: Lys, Met and Thr, (i.e., PC (22% CP, 2.34% Lys, 0.72% Met and 1.80% Thr), PC-Lys (22% CP, 1.64% Lys, 0.72% Met and 1.80% Thr), PC-Met (22% CP, 2.34% Lys, 0.50% Met and 1.80% Thr), and PC-Thr (22% CP, 2.34% Lys, 0.72% Met and 1.26% Thr)). Calves were fed thrice daily; starter (20% CP, 1.03% Lys, 0.30% Met and 0.69% Thr), hay (3.23% CP, 0.29% Lys, 0.12% Met and 0.23% Thr) and water were offered free choice. Starter and hay were only offered beginning on d 36 (after 5 wk) and d 43 (after 6 wk), respectively. BW, body size and blood samples measures were taken every two weeks. Three-day total collection of feed refusals, feces, and urine were recorded starting at d 33 and d 54 of age, respectively. From the results, the limiting sequence and relative ratio between the 3 AAs in calves with different diet structures were calculated. The limiting sequence of the 3 AAs were ranked as Lys, Met and Thr; the proper ratio was 100:29:70 for MR-only diet and 100:30:60 for diets consisted of MR, starter and hay. Nitrogen digestion and utilization and nutrient digestibility were negatively affected by AA deletion treatments. From the evidence of this experiment, it did not appear that the AA limiting sequence was selectively altered by differences in diet structures such as would be encountered in practice. The relative ratio between the 3 AAs varied with the offer of starter and hay to calves, and the average ratio was 100:29.5:65 for calves during 2 to 10 wk of age.